Banach-Saks Type and Gurariǐ Modulus of Convexity of Some Banach Sequence Spaces. (26th March 2014) - Hudzik, Henryk; Karakaya, Vatan; Mursaleen, Mohammad; Simsek, Necip
Abstract : Banach-Saks type is calculated for two types of Banach sequence spaces and Gurariǐ modulus of convexity is estimated from above for the spaces of one type among them.